2014
DOI: 10.1126/science.1257481
|View full text |Cite
|
Sign up to set email alerts
|

High thermodynamic stability of parametrically designed helical bundles

Abstract: We describe a procedure for designing proteins with backbones produced by varying the parameters in the Crick coiled coil-generating equations. Combinatorial design calculations identify low-energy sequences for alternative helix supercoil arrangements, and the helices in the lowest-energy arrangements are connected by loop building. We design an antiparallel monomeric untwisted three-helix bundle with 80-residue helices, an antiparallel monomeric right-handed fourhelix bundle, and a pentameric parallel left-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
300
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 269 publications
(307 citation statements)
references
References 35 publications
(23 reference statements)
2
300
0
Order By: Relevance
“…It has previously been suggested that heterochiral α-helical interfaces can occur over only about four heptad repeats before core side chains diverge from the interhelical interface; however, we speculate that longer and likely more stable interfaces could be formed between L-and D polypeptides containing nonheptad sequence repeats. Recent work has shown that native and designed L polypeptides harboring a hendecad sequence pattern, either alone or in combination with the heptad repeat, can form homochiral quaternary assemblies with little or no supercoiling (50,53). This trend is significant in the context of heterochiral assemblies because oligomers formed between L-and D polypeptides are expected to be incompatible with α-helical supercoiling.…”
Section: Discussionmentioning
confidence: 97%
“…It has previously been suggested that heterochiral α-helical interfaces can occur over only about four heptad repeats before core side chains diverge from the interhelical interface; however, we speculate that longer and likely more stable interfaces could be formed between L-and D polypeptides containing nonheptad sequence repeats. Recent work has shown that native and designed L polypeptides harboring a hendecad sequence pattern, either alone or in combination with the heptad repeat, can form homochiral quaternary assemblies with little or no supercoiling (50,53). This trend is significant in the context of heterochiral assemblies because oligomers formed between L-and D polypeptides are expected to be incompatible with α-helical supercoiling.…”
Section: Discussionmentioning
confidence: 97%
“…However, we posited that, in contrast to most natural protein structures, the high stability of de novo -helical barrels and bundles might tolerate this level of change. 35,40 To test this, we adopted an iterative design strategy, fully characterizing point and double mutants en route. …”
Section: Rational Design Of Multiple Active Sitesmentioning
confidence: 99%
“…We demonstrate a high level of design success for ThreeFoil as evidenced by its: (i) reversible, cooperative, two-state (un)folding; and (ii) well folded and functional native structure which has high solubility and monodispersity, well diffracting crystals, and great resistance against H/D exchange (1), denaturation by chaotropes and detergent, and degradation by protease. Although the rational design of proteins with desired structure and function remains a great challenge and often require multiple cycles of design and/or selection to improve them, successes in designing both structures and/or functions, including ones not observed in nature, have been increasing (3,4,6,8,9,18,49,50). These results demonstrate the increasing understanding of fundamental principles and utility of computational protein design.…”
Section: High Chemical and Protease Resistances Of Threefoil And Othementioning
confidence: 83%